Norbornadiene-functionalized triazatriangulenium and trioxatriangulenium platforms - Löw, Roland; Rusch, Talina; Moje, Tobias; Röhricht, Fynn; Magnussen, Olaf M.; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2019)
Triazatriangulenium (TATA) and trioxatriangulenium (TOTA) ions are particularly suited systems to mount functional molecules onto atomically flat surfaces such as Au(111). The TATA and TOTA units serve as platforms that absorb onto the surface and form ordered monolayers, while the functional groups are protruding upright and freestanding from the central carbon atoms. Azobenzene derivatized TATA’s are known to exhibit extremely fast cis→trans isomerization on metal surfaces, via a peculiar non-adiabatic singlet→triplet→singlet mechanism. We now prepared norbornadienes (NBD) and quadricyclanes (QC) attached to TATA and TOTA platforms which can be used to check if these accelerated rates and the spin change mechanism also apply to [2 + 2] cycloreversions (QC→NBD).
Keywords: [2 + 2] cycloaddition; [2 + 2] cycloreversion; norbornadiene; photochemical isomerization; quadricyclane; self-assembled monolayers; TATA platform; thermal isomerization; TOTA platform